Mineralization of paracetamol using a gas diffusion electrode modified with ceria high aspect ratio nanostructures. (1st February 2019) - Pinheiro, Victor S.; Paz, Edson C.; Aveiro, Luci R.; Parreira, Luanna S.; Souza, Felipe M.; Camargo, Pedro H.C.; Santos, Mauro C.
Abstract: A large number of pharmaceutical drugs have been found in effluents because conventional treatments are not efficient in their removal. Among these drugs, paracetamol is a cause of concern due to its great use worldwide. In this context, electrochemical advanced oxidation processes (EAOPs) based on the Fenton process have been studied because they are able to remove these persistent organic pollutants. This work aims to use an electrocatalyst based on Vulcan XC-72 carbon black modified with 1% ceria high aspect ratio nanostructures (1% CeO2 HARN/Vulcan XC-72) as a gas diffusion electrode (GDE) for both hydrogen peroxide electrogeneration and paracetamol degradation using Fenton-like processes. These studies were evaluated using two different anodes, Pt and boron-doped diamond (BDD). The results obtained in the H2 O2 electrogeneration indicated a large increase in the efficiency of the modified gas diffusion electrode (MGDE) with the 1% CeO2 HARN/Vulcan XC-72 electrocatalyst compared to the Vulcan XC-72 GDE without modification. Approximately 1463 mg L −1 of H2 O2 with an energy consumption of 11.5 kWh kg −1 and a current efficiency of 44.9% was obtained. The tested EAOPs showed paracetamol mineralization rates of up to 98.4% after 6 h of electrolysis in 350 mL of acidic medium. The MGDE also showed a high stability without loss of H2 O2 electrogeneration capacity after 130 h of use, making it promising in applications for EAOPs aiming at organic pollutant mineralization. Graphical abstract: Image 1 Highlights: Vulcan XC-72 modified gas diffusion electrode 1% ceria high aspect nanostructures. MGDE shows to be highly stable for H2 O2 electrogeneration. BDD/PEF mineralize from 89.0% to 98.4% of paracetamol. Low Fe 2+ concentrations with high mineralization efficiencies.